Rom/Apulien, Italien: Die Archäologie konjunktureller Bewegungen auf der italischen Halbinsel und im Westen des Römischen Reiches - Pasieka, Paul (e-Forschungsberichte des DAI, 2023)
One important outcome of the extensive recent research of the Roman economy has been the recognition of distinct economic cycles and crises at different times and in different regions. The aim of this project is to give an overview of the existing research of economic cycles and crises in order to extract adequate proxies for economic activity from both the research literature in the archaeological material and especially the indicators of economic crises used to date. A subsequent theoretical reflection of the given theses shall provide a basis for testing the obtained insights utilising appropriate regional examples (central Italy, especially Etruria and northern Lazio, and Apulia). The overall purpose of this dissertation is to reach a new and foremost understanding of the structure of the Roman imperial economy and to reintegrate the important aspects of economic life into predominant socio-political considerations.